1973
DOI: 10.1071/bi9730065
|View full text |Cite
|
Sign up to set email alerts
|

Stress Metabolism III. Variations in Response to Water Deficit in the Barley Plant

Abstract: Barley plants (cv. Prior) were grown in soil in a controlled environment and subjected to one, two, or three cycles of water stress by witholding water for short periods interspersed with periods of adequate water supply. The water potentials of the leaf tissues during and following these periods of stress were unaffected by the previous stress history of the plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
3

Year Published

1979
1979
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 11 publications
5
23
1
3
Order By: Relevance
“…These data confirm the relationships previously observed by several authors between drought tolerance and proline accumulation in cereals (Singh et al ., 1973 ;Monneveux & Nemmar, 1986 ;Narayan & Misra, 1989) . These data confirm the relationships previously observed by several authors between drought tolerance and proline accumulation in cereals (Singh et al ., 1973 ;Monneveux & Nemmar, 1986 ;Narayan & Misra, 1989) .…”
Section: -supporting
confidence: 93%
See 1 more Smart Citation
“…These data confirm the relationships previously observed by several authors between drought tolerance and proline accumulation in cereals (Singh et al ., 1973 ;Monneveux & Nemmar, 1986 ;Narayan & Misra, 1989) . These data confirm the relationships previously observed by several authors between drought tolerance and proline accumulation in cereals (Singh et al ., 1973 ;Monneveux & Nemmar, 1986 ;Narayan & Misra, 1989) .…”
Section: -supporting
confidence: 93%
“…Proline accumulation has been noted in most winter cereal species when they are subjected to abiotic stresses : accumulation of proline under water stress has been described in barley (Singh et al ., 1973) as well as in bread (Triticum aestivum) and durum wheat (Monneveux & Nemmar, 1986). The physiological significance of water stress induced accumulation of proline is not clear, and the underlying mechanisms involved in this accumulation are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation between proline accumulation and drought resistance claimed by some workers (e.g. Singh et al, 1973, Karamanos et al, 1983 was not found by others (e.g. Hanson, Nelson & Everson, 1977;Bhaskaran et al, 1985).…”
Section: Discussionmentioning
confidence: 87%
“…Many workers reported that the tolerant plants have a high proline accumulation (Singh et al 1973, Sivaramakrishnan etal. 1988, Gzik 1996.…”
Section: Discussionmentioning
confidence: 99%